الأدلة القرآنية ومناقشتها عند إبراهيم مصطفى فى وضع القواعد النحوية الجديدة فى كتاب إحياء النحو - Lestari, Robby Jundi; Suci, Mimi Permani; Tahir, Tahir (Universitas Muhammadiyah Gorontalo, 2024)
This research aims to discuss the Qur'anic evidence used by Ibrahim Mustafa to develop grammar rules as well as critique some grammatical concepts of previous scholars using the qualitative research method with the type of library research in four ways, namely collecting research data, reading library materials and writing a research note. It edits your research notes. The researcher used the method of data analysis content analysis aimed at obtaining Quranic evidence and new ideas of Ibrahim Mustafa in the book Revival of Grammar. The results of this research from the verses of the Holy Qur'an that Ibrahim took for discussion, support and development of rules in his book Revival of Grammar found from the surahs in the Qur'an in Surat Taha: 63, Muhammad: 22, Al-Baqarah: 246, Al-Baqarah: 2, Al-Baqarah: 32, Al-Baqarah: 193, Al-Baqarah: 256, Al-Ma'idah: 109, Yunus: 64, Yusuf: 92, Thunder: 11 , Al-Baqarah: 112, 262, 277, Al-Baqarah: 254, Al-Ma'un: 6-7, Al-Baqarah: 102, Al-Baqarah: 2, Hud: 43, Muhammad: 144, sixteen and one hundred (116) any of Surat Al-Baqarah and twenty-nine verses in Surat Al-Isra for the name (no). As for his ideas made, which is a noun that is raised is not erected, the noun (not) is erected after not singular and raised after (not) is repeated, and the dependents are two types and not the conjunctions followed, and the use of no with the verb is more common than the noun, and the present tense verb for the past tense, and the missing sentence.